LITERATURE ANALYSIS REVIEW APPLICATION PROBLEM BASED LEARNING (PBL) LEARNING MODEL ON INDONESIAN LANGUAGE LEARNING IN ELEMENTARY SCHOOLS - Anggun Oktaria; Nathania Alfitri L; Maudi Dwi Pratiwi; Riskina Sri Martati (Teaching and General Education Studies, 2025)
This qualitative research in the form of a literature review or literature study was carried out because elementary school teachers were not familiar with the current learning model, such as the Problem-Based Learning (PBL) model, for Indonesian language learning. The literature study approach is used in the research process. Based on a literature review that has been conducted in ten research journals on the use of the model in Indonesian learning in elementary school, it can be concluded that the PBL model can have a positive influence on high classes (70%) and low classes (30%). Based on the results of a literature review conducted on ten research journals on the use of the model in Indonesian learning in elementary school, it can be concluded that the PBL model can have a positive influence on high classes (70%) and low classes (30%). Based on the results of the study, the use of the PBL model for Indonesian learning in elementary school has several benefits, namely increasing learning activities (30%), improving learning outcomes (50%), fostering critical thinking skills (10%), and fostering creative thinking skills (10%).